2003
DOI: 10.1007/s10238-003-0020-1
|View full text |Cite
|
Sign up to set email alerts
|

The C(-260)>T gene polymorphism in the promoter of the CD14 monocyte receptor gene is not associated with acute myocardial infarction

Abstract: CD surface molecules mediates cell activation and signaling. In particular, CD14 on blood monocytes mediate monocyte/macrophage activation by lipopolysaccharide. Lipopolysaccharide and its receptor, CD14, have been implicated in atherogenesis. It has been recently shown that a C(-260)T polymorphism in the promoter of the CD14 receptor may be a risk factor for coronary artery disease. Recently this association has been questioned because no increased risk was found with the T allele, even in the homozygous stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 19 publications
1
12
4
Order By: Relevance
“…But this association has not be found in other studies [13,15,16]. Since the deleterious influence of smoking on acute vascular events has been extensively demonstrated [31] and in the light of the interaction observed between (C(À260)!T) polymorphism in CD14 gene and current smoking in sCD14 levels, it would be of interest to determine whether (C(À260)!T) polymorphism in CD14 gene may act as a mediator between the effect of smoking and acute vascular events.…”
Section: Influence Of Cd14 Gene Polymorphism (C(2q260)!t) On Stable Acontrasting
confidence: 53%
See 1 more Smart Citation
“…But this association has not be found in other studies [13,15,16]. Since the deleterious influence of smoking on acute vascular events has been extensively demonstrated [31] and in the light of the interaction observed between (C(À260)!T) polymorphism in CD14 gene and current smoking in sCD14 levels, it would be of interest to determine whether (C(À260)!T) polymorphism in CD14 gene may act as a mediator between the effect of smoking and acute vascular events.…”
Section: Influence Of Cd14 Gene Polymorphism (C(2q260)!t) On Stable Acontrasting
confidence: 53%
“…In human pathology, an association has been found between a polymorphism in the promoter of the receptor CD14 (C(À260)!T) and the risk of acute vascular events (myocardial infarction and stroke) in some selected populations [9][10][11][12]. But this association has not been found in other studies [13][14][15][16] and no significant correlation has been observed with stable coronary heart disease [17]. Also, divergent results have been reported on the relationship between this polymorphism and expression of sCD14 [14,17,18].…”
Section: Introductionmentioning
confidence: 92%
“…This support the role of CD14 promoter polymorphism in atheromatous plaque vulnerability. Contrarily, other studies have not corroborated these findings and showed a lack of association between C(-260)T CD14 promoter and susceptibility to atherosclerosis and risk of MI [65][66][67]. Finally, a recent study, performed in a central Italy elderly population with atherosclerotic carotid stenosis, showed an increased TT homozygote frequency of C-260T polymorphism, providing insight into the pathogenetic role of this polymorphism in atherosclerosis [68].…”
Section: Ccr5mentioning
confidence: 86%
“…Recent studies found no association between allele and genotype distributions of CD14 promoter polymorphism and the risk of MI. [67][68][69][70] The discrepancies between these negative studies and those where an association has been found may be explained by a different ethnic background of the study population and the use of subgroup analysis. Moreover, most of the CD14 studies were cross sectional and not prospective studies.…”
Section: Cd14 Promoter Polymorphism and Atheromatous Plaque Instabilitymentioning
confidence: 93%